ПРОБЛЕМНОЕ ОБУЧЕНИЕ - КАК ОДИН ИЗ ИННОВАЦИОННЫХ ТЕХНОЛОГИЙ ОБУЧЕНИЯ ИДИОМАТИЧЕСКИМ ВЫРАЖЕНИЯМ АНГЛИЙСКОГО ЯЗЫКА СТУДЕНТОВ ФИЛОЛОГОВ - Калабаева, М.А. (SCIENCE and SOCIETY, 2023)
Today the problem-based learning technology is actively used in solving a fairly wide range of issues of teaching foreign languages, although there is no experience of its use for the formation and improvement of idiomatic competence in the modern linguodidactic paradigm.